Creating Domestic Capital Markets in Developing Countries : Perspectives from Market Participants - Demekas, Dimitrios G. (International Finance Corporation, Washington, DC, 2020)
Domestic capital markets that are deep, efficient, and well-regulated can create access to long-term, local-currency finance. Interviews with market participants reveal four important findings. First, there are two distinct phases of capital market development, an embryonic phase in which the government is predominant and a mature phase in which the capital market starts to serve the private sector. Each phase has distinct preconditions and drivers that determine the success of capital market development. Second, capital market development requires continuous monitoring and policy interventions due to changing market stages, some of them stable but suboptimal. Third, while capital markets are a crucial source of large volume, long-term local currency finance, they often fail smaller countries and companies. Finally, as the capital market develops, intangible or ‘soft’ factors become more important, including financial sophistication, a culture of trading and risk-taking, the quality of human capital, and an appreciation of transparency.